Environmental factors enabling occupational well-being of adolescents living in Groendal community - Du Preez, Jani (University of the Free State, 2019)
Introduction: The occupational well-being of people is directly influenced by their physical- and social environments. Adolescents living in communities with limited resources are exposed to environmental factors that can cause occupational injustice due to limited occupational possibilities. However, within each community there are resources that can be utilised to enable occupational well-being, despite the effects of poverty. The community of Groendal, in the Western Cape of South Africa, is such a community whose adolescents’ occupational well-being can be enabled through their environment, despite the occupational restrictions presented by limited resources. Purpose: The main problem that motivated this study was that despite the known realities of occupational restrictions facing adolescents in the community of Groendal due to limited resources, no contextually situated information was found about environmental factors that the adolescents viewed as enabling to their occupational well-being. This is problematic in the light of the ‘community-built practice’ approach, which states that a strength-based approach is necessary when occupational therapists want to contribute to community development in a way that is authentic and inclusive and emphasise the importance of hearing the subjective voices of community members. In response to this problem, this study aimed to describe which physical- and social environmental factors adolescents living in Groendal viewed as enabling to their occupational well-being. Methodology: Q methodology, a mixed methods study design, was chosen as the most suitable methodology for this study. Q methodology has a specific focus on studying the subjective viewpoints of participants. Thirty-three adolescents from the community of Groendal, aged 13 to 17 years, participated in this study. Participants of this study were provided with 39 cards of typed environmental factors from the Groendal community. The participants were asked to sort these cards onto a grid, indicating which environmental factors enabled their occupational well-being the most, and which ones enabled it the least. After sorting the cards, participants answered open-ended questions to clarify why they sorted their cards in a specific manner. Hence, after data analysis, quantitative and qualitative data were extracted for interpretation. Findings: The results from the quantitative and qualitative data were holistically interpreted which presented four environmental enablers to occupational well-being according to adolescents from Groendal. These four environmental enablers were: 1) Immediate families, 2) Educational resources, 3) Recreational resources and 4) Basic resources. The data from the open-ended questions provided a deeper understanding of why the participants viewed these four environmental factors as enablers to their occupational well-being. Immediate families were described as enablers to occupational well-being, because they: contributed to forming moral values, provided educational opportunities, met physical needs and provided social support. Educational resources were described as enablers to occupational well-being, because they provided opportunities for a better future, knowledge and emotional support. Recreational resources were described as enablers to occupational well-being, because they provided broader occupational choices and provided opportunities for a better future. Lastly, basic resources were described as enablers to occupational well-being, because they formed a baseline from which occupational well-being could be achieved. Conclusions: The main value of this study was that it provided contextually situated information about adolescents’ (living in Groendal) subjective views on which environmental factors enabled their occupational well-being. This information could be helpful, since it provides a point of departure for a community-built practice approach in the community of Groendal, with limited occupational therapy involvement to date. The information is strength-based, which aligns with the community-built practice approach.
Dissertation (M.Occupational Therapy)--University of the Free State, 2019
Keywords: Occupational well-being; Environmental factors; Adolescents; Community